2015
DOI: 10.4028/www.scientific.net/amm.813-814.597
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Effect of Nickel Content on Hardness, Optimum Aging Temperature and Aging Time for Spinodal Bronze Alloys Cast in Metal Mould

Abstract: An investigation was conducted to find the optimum aging temperature and aging time for Cu-Sn-Ni spinodal bronze alloys with varying nickel wt% cast in metal mould. The specimens were subjected to solutionisation and were aged at 250°C, 300°C, 350°C, 400°C and 450°C to induce spinodal decomposition. The microstructural observation reveals that the dendritic structure of the as-cast alloy was completely eliminated after solutionisation and grain boundary precipitates were formed with increase in aging time. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Sahu et al [ 19 ] reported the microstructural characterization of Cu-15Ni-Sn alloys with different Sn content by X-ray diffraction. Shankar and Sellamuthu [ 20 , 21 ] investigated the effect of Sn or Ni content on hardness, aging temperature, and aging time of Cu-Ni-Sn alloys that were cast in metal mold. Therefore, the aim of the present work is to investigate the effect of Ni content on hardness, yield strength, microstructure and morphology of Cu-xNi-5Sn alloys under the same condition of aging treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Sahu et al [ 19 ] reported the microstructural characterization of Cu-15Ni-Sn alloys with different Sn content by X-ray diffraction. Shankar and Sellamuthu [ 20 , 21 ] investigated the effect of Sn or Ni content on hardness, aging temperature, and aging time of Cu-Ni-Sn alloys that were cast in metal mold. Therefore, the aim of the present work is to investigate the effect of Ni content on hardness, yield strength, microstructure and morphology of Cu-xNi-5Sn alloys under the same condition of aging treatment.…”
Section: Introductionmentioning
confidence: 99%